The Variety of Lengger Banyumas’ Performances - Bugov, Dobrin Tsvetanov (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2024)
This article aims to center on the variety of styles of lengger - a traditional art found in Banyumas, Central Java, Indonesia. The article offers a new approach towards understanding lengger by indicating the development that underwent in the performance structure. The study was conducted in Banyumas, Central Java, Indonesia for the period of over a year, between 2022 and early 2024. Using qualitative approach, this study is aimed to explore the variety of the dance practiced by local actors. By using qualitative approach, data was collected using in-depth and semi-structured interviews and participatory observation. There are 13 participants that participated in this study, consisting of local figures engaged in various lengger activities, such as dancers, teachers, and owners of dance studios. The study indicates that lengger evolved greatly in terms of its dance performance. In order to demonstrate this, I use “dance fragments” – a specific moments of performance, time and space to indicate the development of the art’s structure, based on personal etnographic study. Nine varieties of lengger were identified – lengger klasik, lengger barangan, lengger resmi, lengger muslimah, lengger garapan, lengger calung barasai, lengger selingan, lengger campursari, and lengger modern. Pointing out the various styles of lengger helps further understand the cultural processes and current trends of the society in Banyumas. Having these changes in its structure where dominant trends overshadow the traditional understanding is a way of keeping the art alive, while lengger’s peaceful cohabitation with other arts speaks about the tolerant nature of people in Banyumas.